The Effect of Visual Mnemonics and the Presentation of Character Pairs on Learning Visually Similar Characters for Chinese-As-Second-Language Learners - Chang, Li-Yun; Tang, Yuan-Yuan; Lee, Chia-Yun; Chen, Hsueh-Chih (Frontiers in Psychology, 2022)
This study investigates the effects of visual mnemonics and the methods of presenting learning materials on learning visually similar characters for Chinese-as-second-language (CSL) learners. In supporting CSL learners to build robust orthographic representations in Chinese, addressing the challenges of visual similarity of characters (e.g., 理 and 埋) is an important issue. Based on prior research on perceptual learning, we tested three strategies that differ in the extent to which they promote inter-related attention to the form and meaning of characters: (1) Stroke Sequence, a form-emphasis strategy, (2) Key-images, a form+meaning strategy utilizing visual code, (3) Pithy Formulas with Key-images, a form+meaning strategy combining visual and verbal codes. A pretest-posttest equivalent-group design was adopted. The independent variables were the learning strategy, the method of presenting character pairs (visually similar vs. dissimilar), and testing time. The dependent variables were learners’ proportions of accurate responses in reading and writing Chinese characters through a posttest (immediately performed after learning) and a delayed posttest (one week after learning); a learner experience survey was also administered to investigate learners’ opinions toward each strategy. Sixty-six non-beginning learners of Chinese participated; they were randomly assigned to one of two groups in which participants learned ten characters via the three strategies, respectively, differing between whether characters were presented in similar pairs or dissimilar pairs. Data were analyzed via three-way ANCOVAs. The Pithy Formulas with Key-images and the Key-images generally yielded higher writing accuracy than Stroke Sequence immediately after learning. Notably, the advantage of the Pithy Formulas with Key-images (verbal and visual) over the Key-images (visual) on writing was specific to participants that learned with visually similar pairs, rather than those that learned with dissimilar pairs. All strategies were effective for reading, yet learners’ experience ratings favored the two form+meaning strategies over the strategy that focuses primarily on form. Suggestions for future research and pedagogical implications on learning visually similar characters were offered.